Naturally absorbed lithium may prevent suicide attempts and deliberate self-harm while eicosapentaenoic acid may prevent deliberate self-harm and arachidonic acid may be a risk factor for deliberate self-harm: The updated different findings in new analyses - Izumi, Toshihiko; Kanehisa, Masayuki; Terao, Takeshi; Shiotsuki, Ippei; Shirahama, Masanao; Satoh, Moriaki; Muronaga, Masaaki; Kohno, Kentaro; Hirakawa, Hirofumi; Etoh, Masaki; Matsukawa, Takehisa (Frontiers in Psychiatry, 2022)
Since our previous investigation on the effects of trace lithium, eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and arachidonic acid (AA) on deliberate self-harm and suicide attempts with adjustment for each other in 2018, to our knowledge, no replication study has been conducted on this topic although this seems very important. In the present study, we increased the number of patients from 197 to 234 and re-analyzed the data in a different way to avoid multicollinearity. The 234 patients included 39 patients who had attempted suicide, 29 patients with a history of deliberate self-harm, and 166 control patients. All patients were transferred to a university emergency department or the psychiatric medical center of a prefectural hospital after suffering from intoxication or injury, were aged 20 or more years, and were alive at the start of the study. We excluded patients with schizophrenia and those receiving lithium therapy or omega-3 supplementation. As a result, higher log-transformed lithium levels were significantly associated with fewer suicide attempts and fewer deliberate self-harm; higher log-transformed EPA levels were significantly associated with fewer deliberate self-harm; and higher log-transformed AA levels were significantly associated with more deliberate self-harm. As limitations, the participants were suicide attempters and not suicide completers, and the present findings cannot be extrapolated to suicide completers. Moreover, the increased number of patients from the previous study was not so many. Nonetheless, the present results were clearly different from the previous ones by new statistical analyses to avoid multicollinearity. In conclusion, the present findings suggest that lithium may be protective against suicide and deliberate self-harm while EPA may be protective against deliberate self-harm, and that AA may be a risk factor for deliberate self-harm.